Mecanismos de ação da Punica Granatum l. durante a vitrificação de tecido ovariano - Martins, Solano Dantas (2024)
Cryopreservation of gametes and embryos has been presented as a viable alternative for preserving fertility in cancer patients. However, it is not an option for pre-pubertal young people and patients who, for other reasons, need immediate treatment. In this context, the most appropriate protocol for these patients is cryopreservation of ovarian tissue and subsequent autotransplantation. However, cryopreservation is a technique that, despite being effective, still has limitations due to the high damage caused to follicular cells and oocytes, resulting from the formation of reactive oxygen species (ROS). Therefore, the present study aimed to evaluate the effects of the ethanolic extract of Punica granataum L. during vitrification of bovine ovarian tissue, verifying its antioxidant capacity, impacts on follicular morphology and ultrastructure. The activity of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) was also analyzed, in addition to the levels of thiol, malonaldehyde (MDA) and nitrite. For this, ovaries from 12 animals were used, which were fragmented and vitrified in the absence (α-MEM; Sucrose; Dimethylsulfoxide and fetal bovine serum) or in different concentrations of the ethanolic extract of Punica granatum L. (10, 50 and 100µg/mL) , for 5 days, followed by heating. The tissues were evaluated immediately after heating and also after being incubated in vitro for 24h. For statistical analyses, the Shapiro-Wilk normality test was performed, followed by twoway analysis of variance (ANOVA), with Tukey post-hoc. Qualitative data were evaluated by chi-square (χ2) using Graphpad Prism 9.0 (Graphpad Software, Inc., San Diego, USA). Statistical significance was considered when the results presented a probability of occurrence of the null hypothesis of less than 5% (P<0.05). As a result, it was observed that the addition of 10 µg/mL of Punica granatum L. ethanolic extract promoted the maintenance of follicular morphology after heating. However, this preservation was not observed in in vitro incubation, with a decrease in the number of normal follicles (P<0.05). On the other hand, it was possible to observe the maintenance of the density of stromal cells and the extracellular matrix (ECM). Furthermore, ultrastructural analysis demonstrated the degeneration of organelles present in vitrified follicles. When evaluating the redox profile, no significant differences were observed in the activity of the CAT and GSH-PX enzymes, in both periods evaluated. However, after 24h of incubation, the concentration of 10 µg/mL promoted greater SOD activity. At the same time, maintenance of MDA levels was observed (P<0.05). In conclusion, the addition of 10 µg/mL of Punica granatum L. ethanolicextract maintained preserved follicular morphology, promoting an increase in the activity of antioxidant enzymes and reducing lipid peroxidation.